2015
DOI: 10.1007/s40095-015-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Lucrative future of microalgal biofuels in Pakistan: a review

Abstract: Pond-grown microalgae have been considered as feedstocks for production of biodiesel. Various natural habitats and man-made environments can be exploited to cultivate microalgae without utilizing arable land which is already decreasing due to urbanization and industrial development. Suitable temperature, solar illumination and availability of phosphorus and nitrogen-rich organic wastes result in algal blooms in stagnant water and river bank's associated pools in many regions including Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 75 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…However, the costs of microalgal biomass production need to be reduced. It has been reported that many microalgal species show potential to grow on various agro‐industrial wastes . Moreover, it has also been reported that photomixotrophic cultivation leads to high cellular fatty acid content .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the costs of microalgal biomass production need to be reduced. It has been reported that many microalgal species show potential to grow on various agro‐industrial wastes . Moreover, it has also been reported that photomixotrophic cultivation leads to high cellular fatty acid content .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many microalgal species show potential to grow on various agro-industrial wastes. [13][14][15][16] Moreover, it has also been reported that photomixotrophic cultivation leads to high cellular fatty acid content. [17][18][19] The capability of microalgae to grow on organic carbon substrates increases the likelihood of implication of lignocellulosic wastes/feedstocks which in turn increases net productivity and decreases cultivation costs.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural wastewater with different animal wastes (poultry and cow) are rich with nutrients. So it can be utilized as growth medium for microalgae cultivation (Manzoor et al, 2015). Eladel et al, (2019), reported that there was a significant increase in lipid productivity of Chlorella sorokiniana cultivated on municipal wastewater over that of Bolds basal medium (BBM) and attributed that increase to the availability of organic compounds in wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Scenedesmus were found to be the most suitable for cultivation in waste water systems to produce alternative fuels such as biodiesel and biogas [48]. Additionally, agricultural and industrial waste water along with different animal wastes (poultry and cow) as growth medium (rich with nutrients) were used for microalgae cultivation and significant increases in lipid content and biomass yield were observed in mixotrophic conditions [49]. wastewater as a growth medium.…”
Section: Algal Biodiesel Research (Studies Conducted On Indigenous Spmentioning
confidence: 99%
“…The influent and effluent dissolved oxygen levels were 0.42 mg/L and 0.36 mg/L respectively. The quantitative analysis showed algal biomass yield as 0.381 g/L and the total lipid content was 10-15 % by weight, extracted by the Bligh and Dyer method (unpublished results).The fresh water species such as Chlorella vulgaris and Scenedesmus are the most promising species of microalgae that can be cultivated in Pakistan, with favourable climatic conditions for their growth[49] and suggest potential to produce biodiesel[53]. It was observed that chlorella vulgaris has high flexibility to adapt to diverse culture conditions and was tested as a biofuel feedstock that can be cultivated under phototrophic and heterotrophic conditions, and the biodiesel produced from it complies with international biodiesel standard ASTM D6751 and European standard EN-14214.…”
mentioning
confidence: 99%